The impact of 'studentification' on the rental housing market - Mira G. Baron; Sigal Kaplan (European Regional Science Association (ERSA), 2010)
Recent 'studentification' processes raise issues regarding the positive and negative impacts of student influx on the urban environment. The positive impacts discussed in the literature include urban core revitalization, employment generation and economic growth. The negative externalities comprise the formation of temporary sub-communities, competition with low-income groups in the rental housing market, and an increase in traffic volume. The current study adds to the literature by focusing on the influence of student influx on rent prices. The importance of this issue derives from the need to understand the net effect of the contradicting impacts of 'studentification' on contemporary urban development for policy implications. While student influx is considered a promising force of urban regeneration, in the literature concerns were raised regarding the detrimental effect of students' temporary sub-communities. The impact of 'studentification' on rent prices is evaluated by hedonic property price analysis incorporating spatial correlations. Data were collected from on-line real-estate portals advertising apartments for rent in the city of Haifa, Israel. The data include apartments characterized by more than a dozen relevant attributes to rental apartment choice including rent price, location, structural features, furniture and electrical appliances. Locations with high proportions of students in the private rented sector were identified on the basis of municipal tax files, as students in Haifa are eligible for substantial municipal tax discounts. The results of this study show the rent price differential between apartments of comparable characteristics located in 'studentified' and 'non-studentified' zones. The paper concludes with a discussion regarding the policy implications of the findings.
Keywords: 330